Solution Approaches for Reverse Logistics Considering Recovery Options: A Literature Review - (:unkn) unknown (IGI GLOBAL, 2019)
Reverse logistics stands out as a rapidly gaining concept due to its contribution to both the environment and the economy. There are many problems with reverse logistics. The decision of recovery options is a fundamental issue that serves many purposes. Choosing the right recovery option will also provide the environmental and economic contribution to maximize the benefits. For this purpose, many solution approaches have been produced for different objectives, which are based on the selection of better recovery options. Since solution approaches are directly interacting with problem models and objectives, it is important to determine an appropriate approach to achieve better results. Until now, many different approaches have been implemented, and results are shared. This chapter systematically examines these solution approaches and reveals the achievements in the literature in order to provide directions for future studies.
Keywords: LOOP SUPPLY CHAIN; OF-LIFE PRODUCTS; NETWORK DESIGN; DECISION-MAKING; STOCHASTIC-MODEL; SYSTEM; UNCERTAINTY; CHANNEL; DEMAND; FUTURE